PROGRAM GAPURA DI SD NEGERI 24 PANGKALPINANG (EVALUASI MODEL STAKE) - Suryadin, Asyraf; Manda Laila K, Febriana; Wulandari, Gita; Widiyanti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This evaluation aims to measure the effectiveness of the program GAPURA (Anti-Bullying and Child-Friendly Movement) at SD Negeri 24 Pangkalpinang is willing to implement the model Bet evaluation. This program was initiated as a response against high and decreasing cases of bullying school safety climate. Approach used is study descriptive with qualitative paradigm, analyzing data through three Stake components: Antecedents (initial and improving conditions sarpra), Transaction (anti-bullying education process, implementation of inclusive learning, and development extracurricular), and Results (final results). Evaluation results shows a positive impact in the form of decreasing numbers bullying (to 4.17%) and violations of discipline (to 7.019%), increased school safety climate of 0.46 as well as an increase in academic achievement in the field numeracy is 30%. The best achievements are seen in components of student character. Overall, Program GAPURA is proven to make a positive contribution significant in creating a good school environment safe, conducive and supports the growth and development of children's rights optimally, although it still requires improvement sustainable.